Integrated plasma scenario analysis for the HL-2M tokamak. (5th November 2019) - Xue, L.; Garcia, J.; Zheng, G.Y.; Hoang, G.T.; Artaud, J.F.; Duan, X.R.; Li, J.X.; Giruzzi, G.; Zou, X.L.; Pan, W.; Zhang, J.H.; Huang, M.; et al.
Abstract: HL-2M is a new medium-sized tokamak under construction at the Southwestern Institute of Physics, dedicated to supporting the critical physics and engineering issues of ITER and CFETR. Analyzing integrated plasma scenarios is essential for assessing performance metrics and foreseeing physics as well as the envisaged experiments of HL-2M. This paper comprehensively presents the kind of expected discharge regimes (conventional inductive (baseline), hybrid and steady-state) of HL-2M based on the integrated suite of codes METIS. The simulation results show that the central electron temperature of the baseline regime can achieve more than 10 keV by injecting 27 MW of heating power with a plasma current of I p   =  3 MA and Greenwald fraction f  G   =  0.65, with the thermal energy and β N reaching 5 MJ and 2.5, respectively. The hybrid regime with f  ni   =  80%–90% can be realized at I p   =  1–1.4 MA with f  G around 0.5, where β N is 2.3–2.5 with H 98 ( y  , 2)  =  1.1. Because of the effect of the on-axis NBCD, the hybrid steady state, at I p   =  1.0 and 1.2, can be achieved more easily than the steady state regimes with reversed shear, corresponding to β N   =  2.6 and 3.4. Such studies show that HL-2M is a flexible tokamak with a significant capacity for generating a broad variety of plasmas as a consequence of the different heating and current drive systems installed.